Le bruit qui court : rumeur et contagion dans Deerbrook (1839) de Harriet Martineau - Marie Duic (Cahiers Victoriens et Edouardiens)
While Harriet Martineau (1802-1876) made a name for herself with her works dedicated to the transmission and popularisation of knowledge, as was the case of her Illustrations of Political Economy (1834) which brought her an almost overnight fame, in her first novel Deerbrook (1839) she is concerned with yet another form of transmission : that of rumours and of epidemics. This article offers to read conjointly these two phenomena relying on a common principle of contagiousness within the social body, whether it be in a literal, pathological sense in the case of epidemics, or in a metaphorical sense when it comes to rumours. Thus I propose to analyse the epidemic qualities of rumours, and conversely the rumour-like aspects of the epidemic that is to be found in the novel. Furthermore, the idea of transmission, which is central to the novel, echoes Martineau’s position as a committed writer and questions her use of fiction for didactic purposes.